Perencanaan Main Engine dan Propeller pada Kapal Pencalang 15 GT - Rama Kurniadhani Atmaja; Abdul Gafur; Bambang Antoko (Proceedings Conference on Marine Engineering and its Application, 2023)
Planning for the selection of the propulsion system on the Pencalang 15 GT ship is carriedout in order to avoid any errors in determining the main engine and propeller. Calculation ofresistance and ship engine power requirements is carried out using the Holtrop method in modelingsoftware to select the appropriate main engine. The propeller selection is carried out with theconsideration that it does not exceed the maximum diameter limit and the propeller does notexperience cavitation. Matching points are carried out by plotting engine power, engine speed andpropeller load characteristics in trial and service conditions with the highest percentage of matchingpoint values.